Castor Oil in Bowel Preparation Regimens for Colon Capsule Endoscopy: A Systematic Review with Meta-Analysis - Ulrik Deding; Sofie Sajan Jensen; Benedicte Schelde-Olesen; Lasse Kaalby; Thomas Bjørsum-Meyer; Anastasios Koulaouzidis (Diagnostics, 2022)
Completing colon capsule endoscopy (CCE) investigations rely on successful transit and acceptable bowel preparation quality. We investigated the effect of adding castor oil to the CCE bowel preparation regimen on the completion rate using a meta-analysis of existing literature. We conducted a systematic literature search in PubMed, Web of Science, and Embase. Included studies underwent quality assessment, and data for meta-analysis were extracted. Pooled estimates for excretion rate and acceptable bowel preparation rate were calculated. We identified 72 studies matching our search criteria, and six were included in the meta-analysis. Three of the studies had control groups, although two used historical cohorts. The pooled excretion rate (92%) was significantly higher in patients who received castor oil than in those who did not (73%). No significant difference in acceptable colonic cleanliness was observed. Castor oil has been used in a few studies as a booster for CCE. This meta-analysis shows the potential for this medication to improve excretion rates, and castor oil could be actively considered in conjunction with other emerging laxative regimens in CCE. Still, prospective randomized trials with appropriate control groups should be conducted before any conclusions can be drawn. Prospero ID: CRD42022338939.